2007
DOI: 10.1007/s00040-007-0940-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential and realized reproduction by different worker castes in queen-less and queen-right colonies of Pogonomyrmex badius

Abstract: Workers of the Florida harvester ant (Pogonomyrmex badius), the only North American Pogonomyrmex with a polymorphic worker caste, produce males when colonies are orphaned. In this study, we assessed the reproductive potential of workers of each caste group, minors and majors, in the presence and absence of the queen, and tested whether males produced in natural queen-right colonies are derived from workers. Worker size was positively correlated with ovariole number such that major workers had approximately dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…In contrast to honeybee nurses which can produce fertile eggs in queenless conditions and sometimes even in the queen presence, workers are sterile in most Pogonomyrmex species [32]. However, Pogonomyrmex workers can produce trophic eggs which are thought to be the main method of nutrient redistribution because trophallaxis – mouth-to-mouth food transfer - has not been observed in this genus [32]. Interestingly, a recent study in Pogonomyrmex californicus showed that nurses had significantly increased ovarian activity compared to foragers [53], suggesting that trophic eggs are specifically produced by nurses.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast to honeybee nurses which can produce fertile eggs in queenless conditions and sometimes even in the queen presence, workers are sterile in most Pogonomyrmex species [32]. However, Pogonomyrmex workers can produce trophic eggs which are thought to be the main method of nutrient redistribution because trophallaxis – mouth-to-mouth food transfer - has not been observed in this genus [32]. Interestingly, a recent study in Pogonomyrmex californicus showed that nurses had significantly increased ovarian activity compared to foragers [53], suggesting that trophic eggs are specifically produced by nurses.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to honeybee nurses which can produce fertile eggs in queenless conditions and sometimes even in the queen presence, workers are sterile in most Pogonomyrmex species [32]. However, Pogonomyrmex workers can produce trophic eggs which are thought to be the main method of nutrient redistribution because trophallaxis – mouth-to-mouth food transfer - has not been observed in this genus [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forsyth 1981;Wenseleers & Ratnieks 2006;Dijkstra & Boomsma 2007;Smith et al 2007). In some species, however, functionally monogynous colonies contain additional inseminated queens that can become reproductively active replacement queens after the original queen is lost (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Power to detect worker reproduction Following the protocol of Smith et al (2007), we tested for evidence of linkage of the two loci used for this study. We used both haploid males and diploid workers to test for linkage disequilibrium in colonies where the queen genotype was heterozygous at both loci (four of the seven colonies).…”
Section: Worker Reproductionmentioning
confidence: 99%